Does foliar nutrition influence the pear fruit quality? - Hudina, M.; Solar, A.; Stampar, F. (International Journal of Horticultural Science, 2003)
The influence of the foliar nutrition on the pear fruit quality (Pyrus communis L.) cv. 'Williams' was studied in years 1997 and 1998. We determined the contents of individual sugars (glucose, fructose, sucrose and sorbitol) and organic acids (malic, citric, fumaric and shikimic) by HPLC (High Performance Liquid Chromatography). The sizes of the fruits (diameter, length, weight) were measured as well as the amounts of soluble solids and titrable acids. The experiment comprised two treatments: the foliar nutrition and the control. In the treatment of foliar nutrition the trees were sprayed five times (from May 22 to July 7) with a foliar fertilizer, which contained 15% of P205, 20% of K20, 0.1% of Mn, 0.1% of B and 0.1% of Mo. The foliar nutrition influenced higher quantities of sugars (glucose, sorbitol, soluble solids) and organic acids (malic, citric) but had no effect on the contents of shikimic acid, pH juice and titrable acids. At the treatment of foliar nutrition a trend of decrease in the contents of fructose, sucrose, fumaric acid, boron, and zinc was noticed.